From Samarkand to Chang’an --The Regionality of Sogdian Cultural Identity during the Tang Dynasty - WANG, YANG (2023)
The Sinicization of the Sogdians in China has always been a focus of attention for the Sogdians. The Sogdians traveled eastward from Central Asia along the Silk Road to China and established many settlements to meet their commercial and living needs. After entering China, the Sogdians integrated and adapted to the local culture for a better life. During the Tang Dynasty, the Sogdians were very active. Among the settlements established by the Sogdians, the life of the Sogdians in Xizhou, Dunhuang, Liangzhou, Liuhu Prefectures, and Chang’an is more representative.